Reducing and sharing the burden of bank failures - Cariboni, Jessica (OECD Publishing, 2016)
This report demonstrates that the contingent liabilities associated with efforts to limit the adverse externalities stemming from failures in the European banking sector are substantially decreasing as a result of new regulation. Noting that the implied shifting of losses from taxpayers to bank creditors is desirable, the report recognises that losses do not disappear. It discusses the issue of where bank recovery or resolution bail-in losses may go. It underlines that the sectoral allocation of losses matters, but concludes that our understanding needs to be further developed and that more transparency about the structure of bank creditors would be desirable. Increasing transparency in this regard would, among other things, help assure policy makers that the new tools available can be used effectively and smoothly in actual practice. Also, raising awareness of investors in bail-inable bank debt about the associated risks should enhance the credibility of the bail-in framework